Justin Timberlake justified the videos - Timberlake, Justin, 1981-; Melvin, Chris; Jive Records; Zomba Recording Corporation ([New York, N.Y.] : Jive Records : Zomba Recording Corp., 2003)
A compilation of music videos from Justin Timberlake's music album "Justified" and live performances at MTV Video Music Awards and MTV's TRL live in Times Sqaures.
1. Like I love you (music video) -- 2. Like I love you (MTV's making the video excerpts) -- 3. Cry me a river (music video) -- 4. Like I love you (2002 MTV Video Music Awards performance) -- 5. Like I love you (MTV's TRL live in Times Square performance) -- 6. Cry me a river (MTV's TRL live in Times Square performance) -- 7. Rock your body (music video) -- 8. Rock your body (MTV's making the video -- excerpts) -- 9. Señorita (music video) -- 11. MTV's launch -- excerpts -- 12. 2003 Brit Awards performance -- Bonus video: I'm lovin' it.
Keywords: Music videos; Popular music -- 2001-2010.; Rhythm and blues music; Rock music -- 2001-2010.